Landscape futures : instruments, devices and architectural inventions - Manaugh, Geoff; Nevada Museum of Art (Barcelona : Actar, 2013)
This work travels the shifting terrains of architectural invention, where new spatial devices on a variety of scales - from the handheld to the inhabitable - reveal previously overlooked dimensions of the built and natural environments. From philosophical toys and ironic provocations to a room-sized kinetic mechanism that models future climates, these devices are not merely diagnostic but creative, deploying fictions as a means of exploring different futures.
Published in conjunction with the exhibition held at the Nevada Museum of Art
boek